DETERMINAN PENGELOLAAN ASET DAERAH PADA INSTANSI DI KABUPATEN ACEH BARAT - Nourmaliza (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2020)
This study aims to examine the factors that influence the management of regional assets agencies in West Aceh District. The unit of analysis in this study is all agencies in West Aceh District, amounting to 29 agencies. Each agencies consists of 3 (three) persons who will be the respondent, namely Head of agencies, Finance Administration Officer, and Activity Technical Officer. Sources of data in this study using primary data that is the results of questionnaires obtained from respondents research. While the technique of collecting research data is done by technique of spreading of questionnaire. The analysis method used is Multiple Linear Regression Analysis. The results showed that the factor of human resource competency, internal control system and accounting information system either jointly or separately affect the management of regional assets agencies in the West Aceh District.